Analisis Pendapatan Usaha Ternak Sapi Bali di Kabupaten Sumbawa Nusa Tenggara Barat - Mastar, Syahdi; Wijayanti, Nila; Hamdani, Asrul; Budiman, Iksan; Angkasa, M. Aries Zuhri (Musamus Journal of Agribusiness, 2023)
Bali cattle breeders in the Moyo Hulu District have several problems, namely when entering the rainy season or planting season, breeders experience difficult in finding feed for livestock because most breeders also work as a farmer. There are also problems in terms of production costs, which affect the acceptance and income of cattle breeders. The purpose of this study was to determine the income of Bali cattle business in Marga Karya Village, Moyo Hulu District, Sumbawa Regency. This research was conducted in Marga Karya Village, Moyo Hulu District, Sumbawa Regency. Determination of the sample of respondent breeders using Quota Sampling, namely as many as 45 respondents. Data collection uses 3 strata based on livestock ownership, with 15 respondents in each stratum. Stara 1 = 1-5 cattle. Strata 2 = 6-10 livestock and Strata 3 = >10 livestock. Data analysis uses cost analysis, gross income with livestock dynamics analysis and net income. The results showed that the average gross income earned by Bali cattle breeders from each stratum of livestock ownership was that in strata 1 the farmer's gross income was Rp. 8,400,000/year, in stratum 2 the farmer's gross income was Rp. 12,125,000.- / year, at stratum 3 the gross income of farmers is IDR 15,400,000 / year, with the percentage increase in income from strata 1 to strata 3 of 83.33%. The average net income earned by Bali cattle breeders is that stratum 1 has a net income of IDR 7,910,806/year, strata 2 has an average net income of IDR 11,435,945/year, and strata 3 has a net income of IDR 14,734,644,-/year., with the percentage increase in income from strata 1 to strata 3 of 86.26%.